A double‐blind randomized, multicenter, placebo‐controlled study of itopride in functional dyspepsia postprandial distress syndrome. Issue 8 (31st March 2022) - Carbone, Florencia; Vandenberghe, Alain; Holvoet, Lieselot; Piessevaux, Hubert; Arts, Joris; Caenepeel, Philippe; Staessen, Dirk; Vergauwe, Philippe; Maldague, Philippe; De Ronde, Thierry; Wuestenberghs, Fabien; Lamy, Vincent; et al.
Abstract: Background: Itopride, a mixed D2 antagonist and cholinesterase inhibitor, has prokinetic effects on gastric motility. The Leuven Postprandial Distress Scale is a validated patient‐reported outcome instrument for functional dyspepsia (FD) postprandial distress syndrome (PDS). We aimed to use the LPDS to assess treatment outcome in PDS and PDS/EPS (epigastric pain syndrome). Methods: Patients with PDS, with or without non‐predominant EPS symptoms, were enrolled in an 8‐week double‐blind placebo‐controlled multi‐center trial with itopride (100 mg t.i.d.). Patients completed LPDS diaries and questionnaires to assess treatment response. Mann–Whitney test and mixed models were used. Results: One hundred patients (79% females, 39.1 ± 1.5 yo) were included. No significant difference was observed between treatment arms ( p = 0.6). Compared to baseline, itopride treatment significantly improved the LPDS score ( p = 0.001) and all individual symptoms ( p < 0.0001). In the placebo arm, this was only the case for belching and epigastric pain ( p < 0.05). In an exploratory analysis, outcomes in "pure" PDS ( n = 45) and overlapping PDS/EPS ( n = 55) patients were assessed and showed that the latter subgroup has the largest benefit with itopride compared to placebo ( p = 0.03). Conclusion: Using the LPDS score in a pilot controlled trial in FD, itopride shows no therapeutic benefit over placebo after 8 weeks of treatment. In an exploratory post hoc analysis, itopride but not placebo was associated with improvement of symptoms compared to baseline, and this was most prominent in patients with overlapping PDS/EPS. The efficacy of itopride in this subgroup needs to be evaluated in a large study using the same outcome measure. (clinialtrials.org ref.: NCT04647955). Abstract : Patients with functional dyspepsia/postprandial distress syndrome were enrolled in an 8‐week double‐blind placebocontrolled multi‐center trial with itopride 100mg t.i.d. Itopride significantly improved the symptom score relative to baseline. The benecial effect of itopride on symptoms was higher in patients with overlapping epigastric pain syndrome symptoms, compared to pure postprandial distress syndrome.